Intelligent Imaging Technology Implementation as Terrorism Prevention in Retail Sectors in 21st Century - Bob Foster; Muhamad Deni Johansyah (Universitas Trunojoyo Madura, 2019)
Terrorism is a very dangerous thing and has become a threat both on a national and international scale. Understanding terrorism seeks to instill the seeds of hostility towards a group, government agencies and even the state. Before entering the 21st century terror attacks are blatant in the business sector by sabotaging and damaging public facilities and vital objects. These physical attacks can be prevented by recording personal identities or conducting regular security patrols and placing a large number of security personnel in places of business and places that are considered strategic. However, this is still not optimal where the level of security and the number of personnel are limited in monitoring the place for a long time and are sustainable. The terrorist attacks in the 21st century are different and require different handling. Attacks can be physical or non-physical. On non-physical objects attacks are usually carried out by hacking networks that can damage internet network connections in one area and even one country. Ways to prevent attacks that are physical in nature by utilizing computer vision technology capabilities that are used to record all civil society. An additional feature in this technology lies in the face recognition and pattern matching techniques where a person's face will be searched for unique features. Then from these data will be biometric data, namely data that will not change and disappear. Computer vision algorithms can detect a person's face or object even though it has been modified or changed in physical and color conditions. The advantages of these algorithms are effectively used to record visitor identities and are optimal in recognizing an object with an accuracy of up to 90%. This system is able to help and improve a security feature of a business and tourist area.